2019
DOI: 10.1097/md.0000000000015738
|View full text |Cite
|
Sign up to set email alerts
|

Information experiences, needs, and preferences of colonoscopy patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…In addition, it is difficult to perform an endoscopic evaluation when there is injury to the intestinal mucosa, a frequent problem in IBD [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is difficult to perform an endoscopic evaluation when there is injury to the intestinal mucosa, a frequent problem in IBD [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Given that many patients do not feel adequately informed about the colonoscopy procedure [ 16 ], it is crucial to provide patients with materials to enhance their understanding. In a recent systematic review of enhanced education for bowel preparation (ie, counseling or training sessions, educational booklets, or videos), researchers found that enhanced education methods improve bowel preparation and promote better visualization of the colon in patients preparing for colonoscopy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, our research team developed a project titled “Optimizing colonoscopy procedures and reducing unnecessary and over use” and explored the information needs and preferences of patients undergoing colonoscopy [ 16 ]. On the basis of the expressed needs and inputs from patients and health care providers, we developed revised educational resources for patients considering or preparing for colonoscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is difficult to perform an endoscopic evaluation when there is injury to the intestinal mucosa, a frequent problem in IBD [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%